Produtividade e teor de óleo de cultivares de girassol sob fertirrigação nitrogenada em duas safras agrícolas - Souza, Almir Rogerio Evangelista de (2018)
Sunflower (Helianthus annuus L.) due to its wide adaptation and use has emerged in the world scenario with significant economic potential, mainly in the production of achenes and oil. The expansion of cultivated areas with sunflower in several countries in semi-arid conditions has required adequate fertilization management practices, ensuring satisfactory yields and yields. The nitrogen fertilizations associated with the most productive cultivars have been reported with special attention, since these are indispensable components in the success of the investment. In this sense, experiments were conducted in two agricultural crops in February / May 2016 and 2017, to evaluate the productivity of achenes and oil and the economic responsiveness of fertirrigated sunflower cultivars with nitrogen doses in the northeastern semi-arid region, Mossoró-RN. The plots consisted of five doses (0, 30, 60, 90, 120 kg ha-1) of nitrogen fertilization and in the subplots four sunflower cultivars (Aguará 06, Altis 99, Multissol and BRS 122). Nitrogen doses positively influenced the number, mass, yield of oil and oil, except for the oil content of the sunflower cultivars, in the two agricultural crops. The N dose for the maximum yield of achenes for ‘Multissol’ and ‘BRS 122’ was 81.8 and 86.6 kg ha-1 and for ‘Altis 99’ and ‘Aguará 06’ at the dose of 120 kg ha-1 of N, respectively, in the 2016 crop season. In 2017, ‘Multissol’ and ‘BRS 122’ at a dose of 100.7 and 92.8 kg ha-1 and for Altis 99’ and ‘Aguará 06’, with 120 kg ha-1 of N. The dose of maximum economic efficiency of N is 60 and 70 kg ha-1 for ‘Multissol’ and ‘BRS 122’ cultivars. For oil yield, the maximum doses of 78.0 and 86.7 kg ha-1 of N for cultivars ‘BRS 122’ and ‘Aguará 06’, ‘Multissol’ and ‘Altis 99’ in the dose of 120 kg ha-1 of N in the 2016 harvest. In 2017 ‘BRS 122’ and ‘Multissol’ obtained in the dose of 88.6 and 99.1 kg ha-1 of N, and ‘Altis 99’ and ‘Aguará 06’ with 120 kg ha-1. The cultivar ‘Aguará 06’, obtained higher productivity of achenes and yield of oil in the two agricultural crops. The net margin corresponded to the increase in nitrogen rates, reaching a maximum net margin of R$ 366.89 ha-1 at the rate of 81 kg ha-1 of N for 'BRS122'; for 'Multissol' was R$ 577.41 ha-1 with 118 kg ha-1 of N. For ‘Aguará 06' (R$ 2,124.00 ha-1) and ‘Altis 99' (R$ 976, 66 ha-1) in the dose of 120 kg ha-1 of N in the 2016 harvest. In the 2017 harvest, 'BRS 122' obtained R$ 190.90 ha-1 in the dose of 83.0 kg ha-1 of N and ‘Multisol’ reached R$ 657.50 at the dose of 85.0 kg ha-1 of N; the cultivars 'Aguará 06' (R$ 1,078.00 ha-1) and 'Altis 99' (R$ 957,14 ha-1) in the dose of 120 kg ha-1 of N. The rate of return and the index were positive for all cultivars in the agricultural crops